Analysing the impacts of digital media on financial performance of newspaper companies - Lekadala, Kudakwashe (Midlands State University, 2017)
The Zimbabwe newspaper industry has recently been suffering from financial challenges due to the economic crises and the rise in digital media. It is against this background that the study sought to investigate the impacts of digital media on financial performance of Newspaper Companies. Time series data for the period of January 2011 to December 2013 was regressed using a multi-regression technique the Ordinary Least Squares method (OLS). The e-views 4 software was adopted to make all the necessary estimations. Literature from various scholars who investigated newspaper companies and financial performance was reviewed. The study indicated that there is a negative relationship between financial performance and digital media however other macroeconomic variables like politics and legislation should be taken into consideration.